Autologous saphenous vein and heparin-bonded expanded polytetrafluoroethylene as graft materials for below-the-knee femoro-popliteal bypass in patients with critical limb ischemia: A propensity score-matched analysis. Issue 2 (April 2022) - Dorigo, Walter; Fargion, Aaron; Bassoli, Giulia; Di Domenico, Rossella; Giacomelli, Elena; Piffaretti, Gabriele; Alessi Innocenti, Alessandro; Pratesi, Carlo
Abstract: Objective: To compare the outcomes of heparin bonded expanded polytetrafluoroethylene (HePTFE) and autologous saphenous vein (ASV) in patients undergoing below-knee (BK) femoro-popliteal bypass for critical limb ischemia (CLI). Design: Retrospective single-centre matched case–control study. Methods: From 2003 to 2019, 275 consecutive BK bypasses for CLI were performed, 109 with the ASV and 166 with a HePTFE graft. All the baseline characteristics that were reliably measured and were potentially relevant in the decision-making process were included as confounders in a logistic regression model and the factors that were significantly different between the two groups then used to perform a propensity matching analysis. Propensity score-based matching was performed in a 1:1 ratio to compare outcomes. Arterial hypertension, hyperlipemia, the need for tibial anastomosis at the distal level and the run-off status were the covariates included in the matching. Follow-up outcomes were estimated by Kaplan–Meier methods and compared with log rank test. Results: After propensity matching, 101 HePTFE bypasses were matched with 101 ASV bypasses. The median duration of follow-up was 37 months (range 1–192). The 5-year survival rate was 67.5% (standard error (SE) 0.05) in the HePTFe group and 64.5% (SE 0.06) in the ASV group (p = 0.8, log rank 0.04). Primary patency rates were 38% (SE 0.06) in the HePTFE group and 41% (SE 0.06) in the ASV group (p = 0.7, log rank 0.3). Also assisted primary patency and secondary patency rates did not differ in the two groups. Amputation-free survival was 53% (SE 0.05) in the HePTFE group and 58% (SE 0.06) in the ASF group (p = 0.6, log rank 0.2). Conclusions: HePTFE provided 5-year similar results to those obtained with use of the ASV in equivalent patients with CLI undergoing below-knee or tibial bypass. Highlights: Retrospective single-centre matched case–control study HePTFE and ASV were compared in CLI patients undergoing BK bypass The two materials provided similar 5-years results in equivalent patients HePTFE could be potentially used in all the patients without an optimal ASV The authors support the need for new prospective RCTs